Best practices for vascular arterial access and closure: a contemporary guide for the cardiac catheterization laboratory - Eltelbany, Moemen; Fabbri, Matteo; Batchelor, Wayne B.; Cilia, Lindsey; Ducoffe, Aaron; Endicott, Kendall; Epps, Kelly; McBurnie, Amika; Neville, Richard; Rosner, Carolyn; Sherwood, Matthew W.; Spinosa, David; et al. (Frontiers in Cardiovascular Medicine, 2024)
More than 1 million transcatheter-based cardiovascular procedures across the spectrum of interventional cardiology are performed annually in the United States. With the expanded indications for and increased complexities associated with these procedures, interventional cardiologists are expected to possess the requisite expertise to complete these interventions safely and effectively. While the art of vascular access and closure remains a prerequisite and critical skillset in contemporary practice, there remain significant variations in the techniques employed, resulting in the bleeding and vascular complications encountered in clinical practice. With an increasing recognition of the potential merits to standardized approaches to vascular access and closure, cardiovascular societies have put forth recommendations around best practices for performing these procedures in the cardiac catheterization laboratories. In this review, we aim to: 1) Examine the evolving definitions of bleeding and vascular complications; 2) Review best practices for transradial and transfemoral access and closure, including for large bore procedures; and 3) Highlight knowledge gaps and proposed areas of clinical research pertaining to vascular access which may inform clinical practice and potentially optimize the outcomes of patients undergoing transcatheter-based cardiac and vascular interventions